Soil “Ecosystem” Services and Natural Capital: Critical Appraisal of Research on Uncertain Ground - Baveye, Philippe C.; Baveye, Jacques; Gowdy, John (Frontiers in Environmental Science, 2016)
Over the last few years, considerable attention has been devoted in the scientific literature and in the media to the concept of "ecosystem" services of soils. The monetary valuation of these services, demanded by many governments and international agencies, is often depicted as a necessary condition for the preservation of the natural capital that soils represent. This focus on soil services is framed in the context of a general interest in ecosystem services that allegedly started in 1997, and took off in earnest after 2005. The careful analysis of the literature proposed in this article shows that, in fact, interest in the multifunctionality of soils emerged already in the mid-60s, at a time when hundreds of researchers worldwide were trying, and largely failing, to figure out how to put price tags meaningfully on "nature's services." Soil scientists, since, have tried to better understand various functions/services of soils, as well as their possible relation with key soil characteristics, like biodiversity. They have also tried to make progress on the challenging quantification of soil functions/services. However, researchers have shown very little interest in monetary valuation, undoubtedly in part because it is not clear what economic and financial markets might do with prices of soil functions/services, even if we could somehow come up with such numbers, and because there is no assurance at all, based on neoclassical economic theory, that markets would manage soil resources optimally. Instead of monetary valuation, focus in the literature has been put on decision-making methods, like Multi-Criteria Decision Analysis (MCDA) and Bayesian Belief Networks (BBN), which do not require the systematic monetization of soil functions/services and easily accommodate deliberative approaches involving a variety of stakeholders. A prerequisite to progress in such public deliberations is that participants be very cognizant of the extreme relevance of soils to many aspects of their daily life. We argue that, as long as this prerequisite is satisfied, the combination of deliberative decision-making methods and of a sound scientific approach to the quantification of soil functions/services is a very promising avenue to manage effectively and ethically the priceless heritage that soils constitute.